Does Ethnic Diversity Impact on Risk Perceptions, Preparedness, and Management of Heat Waves? - Siman-Tov, Maya; Vanderplanken, Kirsten; Guha-Sapir, Debarati; van Loenhout, Joris A. F.; Adini, Bruria (Frontiers in Public Health, 2021)
Detrimental health impacts of heatwaves, including excess mortality, are increasing worldwide. To assess risk perceptions, protective knowledge and behaviors concerning heatwaves in Israel, a study was initiated, comparing attitudes of majority (Jewish) and minority (Arab) populations. A quantitative survey was disseminated through an internet panel, to a representative sample of 556 individuals (79% Jews; 21% Arabs). Overall, 74% consider heatwaves a problem, 93% believe that heatwaves’ frequencies will increase, 27% are very concerned about the effects of heatwaves. Higher levels of awareness to heatwaves were found among Jewish compared to Arab respondents; 90% versus 77% (respectively) could name heatwaves’ symptoms (p<.001); 81% versus 56% (respectively) reported knowing how to protect themselves (p<.001); 74% versus 47% (respectively) reported knowing what to do when someone suffers from heat stroke (p<.001). Arab compared to Jewish respondents presented higher levels of concern about heatwaves’ effects (3.22 vs 3.09 respectively; t -2.25, p=0.03), while knowledge of protective measures was higher among Jews compared to Arabs (3.67 vs. 3.56 t=2.13 p=0.04). A crucial component of enhancing preparedness to heatwaves is empowerment of minority as well as majority groups, to strengthen their capacity to implement protective behavior and elevate their self-belief in their individual ability and fortitude.